Piano sonata no. 12 in A-flat major, op. 26 (Simrock) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Kinsky, Ferdinand Johann Nepomuk, Fürst von, 1781-1812:::Former owner:::::::::::: (Germany; N. Simrock; Bonn)
Early edition of the Piano sonata no. 12 in A-flat major, op. 26, published by Simrock, with altered price on title page.